Diagnoza zaburzeń ze spektrum autyzmu dawniej i dziś a możliwości wczesnego wspomagania rozwoju dzieci - Kostecka, Adrianna (Studia Edukacyjne, 2024)
The diagnosis of autism spectrum disorders is based on various activities, e.g. the use of adequate diagnostic tools, conversations with parents, and observation of the child’s behavior. This enables the adoption of an appropriate therapy plan and is the key to making the final diagnosis. Early introduction of developmental support into a child’s life has a positive impact on the development of cognitive functions. The article is devoted to the diagnosis of autism spectrum disorders, various diagnostic tools, and early support for child development. I will present the characteristics and epidemiology of ASD, the diagnostic process of the disorder, the selection of an appropriate diagnostic tool, as well as the theory of early development support and the impact of early introduction of therapeutic activities on the child’s functioning.